Membangun Self-Regulated Learning melalui Kurikulum Berbasis Cinta dan Pembelajaran Digital pada Peserta Didik Madrasah Ibtidaiyah - Rahmawati, Emma; Nurhidin, Edi; Husna, Mujlauwidzatul (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2025)
Self-Regulated Learning (SRL) is an important skill that needs to be developed so that students can manage their learning process independently and responsibly. In practice, strengthening SRL has not been systematically developed in learning, especially when the curriculum and the use of learning media are not integrated. This article examines the growth of SRL through the use of a Love-Based Curriculum (LBC) supported by digital learning media. This study uses a library research method. Data sources consist of books, policy documents, and journal articles relevant to SRL, LBC, and digital learning. The results of the study indicate that integrating LBC and digital learning media fosters a humanistic, emotionally safe learning climate, strengthens values of empathy, responsibility, and self-awareness, and provides flexible, reflective learning spaces. The values of LBC serve as an affective and moral foundation that supports the self-regulation process. In contrast, digital learning media serve as tools that facilitate learning planning, process monitoring, and student reflection. In conclusion, the integration of LBC and the use of digital learning media holistically strengthen SRL in elementary school students and have practical implications for the design of more humanistic, adaptive, and sustainable madrasah learning.